2017
DOI: 10.5535/arm.2017.41.4.573
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Myofascial Pain Syndrome of the Infraspinatus Muscle

Abstract: ObjectiveTo report the characteristics of myofascial trigger points (MTrPs) in the infraspinatus muscle and evaluate the therapeutic effect of trigger-point injections.MethodsMedical records of 297 patients (221 women; age, 53.9±11.3 years) with MTrPs in the infraspinatus muscle were reviewed retrospectively. Because there were 83 patients with MTrPs in both infraspinatus muscles, the characteristics of total 380 infraspinatus muscles with MTrPs (214 one side, 83 both sides) were investigated. Specific charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 20 publications
3
14
0
Order By: Relevance
“…The wide spread of nerve terminals within the IS in the results of this study based on Sihler’s staining support that trigger points can occur at various sites within the muscle. However, the main occurrence site of the trigger point presented in the previous study was mainly the middle part of the muscle 5 14 15. Comparing this with the results from the present cadaver study, it was found that the main trigger point was the muscle belly of the IS.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The wide spread of nerve terminals within the IS in the results of this study based on Sihler’s staining support that trigger points can occur at various sites within the muscle. However, the main occurrence site of the trigger point presented in the previous study was mainly the middle part of the muscle 5 14 15. Comparing this with the results from the present cadaver study, it was found that the main trigger point was the muscle belly of the IS.…”
Section: Discussionsupporting
confidence: 74%
“…In addition, in this study, many intramuscular nerve terminals were observed in the medial third of the IS. Also, according to Kwon et al ,5 since the trigger point is reported to be multiple sites if another injection point is added rather than a single injection point, it is thought that more effective treatment can be promoted in consideration of the spread of BoNT to the surrounding area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because repeated intramuscular injection of local anesthetics results in myotoxicity (49,50), this study used a short-term intervention, 2 weeks of treatment, to compare the effects of SM and TPI treatment. Although prior investigations reported that weekly TPI for 1-2 weeks immediately improved myofascial pain (16)(17)(18)40,51), some studies noted significant decreases in pain scores over 4 weeks after repeated TPI for MTrPs in patients with myofascial pain (43,52,53). Ideally, future studies should assess the effects of repeated TPI and dry needling for longer than 4 weeks on muscle hardness, including the TB.…”
Section: Discussionmentioning
confidence: 99%
“…Physiotherapy, such as stretching and massage treatment, is the most popular treatment for MPS (5,15), and massage treatment for muscles of MPS patients is considered one of the most effective methods for reducing pain and muscle hardness (9). In addition, the use of the local anesthetic lidocaine in trigger point injection (TPI) of MTrPs reduces localized and referred pain and is a mainstay of short-term MPS management (16)(17)(18). However, the outcomes of these MPS treatments have not been carefully evaluated.…”
Section: Introductionmentioning
confidence: 99%